At Your Leisure: Establishing a Popular Reading Collection at UBC Library - Diers, Bailey; Simpson, Shannon (Evidence Based Library and Information Practice, 2012)
Objectives – This study investigated the leisure reading habits and preferences of students, faculty, staff, and community members at the University of British Columbia (UBC) in order to determine if a leisure reading collection would fulfill a need and, if so, what form that collection should take to best serve the population. Methods – This study, conducted in October 2010, consisted of a 19-question online questionnaire distributed to a random sample of UBC undergraduate students, graduate students, faculty, and community library users and an identical, open participation questionnaire for the entire UBC community, including staff and community members. In addition to some demographic information, the questionnaire gathered information about leisure reading habits, tendencies, and the participants’ preferences for a potential future leisure reading collection at UBC Library. Results – There were 467 valid responses out of 473 total responses received from UBC undergraduate students, graduate students, faculty, staff, and community members. Of the valid responses, 244 were received from the 1,500 random sample invitations (a 16.3% response rate). Additionally, the questionnaire was advertised for open participation for those not invited, resulting in the remaining 229 responses. Results of this study indicated overwhelming support for a leisure reading collection at UBC Library, with 94% of respondents stating they might or would use a leisure reading collection. This study also revealed strong leisure reading habits among all response groups. However, only 6% of respondents currently acquire most of their leisure reading materials from UBC Library. Additional analysis found that UBC Library already owns 81% of the titles and authors requested by respondents in the survey. Conclusions – Based on the findings, the strong support for a leisure reading collection, and the fact that many UBC campus residents are not eligible for a free municipal public library card and borrowing privileges, there is a genuine need for a leisure reading collection at UBC Library. The data indicates that if accessible and convenient, a leisure reading collection could provide an opportunity for those who do not already read for leisure to do so. Additionally, a UBC Library leisure reading collection could attract community members, including those who are not UBC Library cardholders. In response to the results of the study, a pilot leisure reading collection was created in September 2011. This will make leisure reading materials easier to access and will allow the Library to further analyze the potential of such a collection, ultimately determining its future.